Ajaran Moral Serat Nitisruti dan Keselarasannya Dengan Surah Al-Qur'an - Intan Puspita; Aris Aryanto; Erlangga Ananta Riesa Wijaya (Kawruh: Journal of Language Education, Literature and Local Culture, 2025)
This study is a qualitative research employing content analysis through Paul Ricoeur’s hermeneutic theory. The main issue examined is the symbolic meaning of moral values in the Serat Nitisruti verses and their relevance to the Qur’an. The researcher limits the discussion to five moral values: compassion, justice, humility, trustworthiness, and sincerity. The text of Nitisruti contains symbolic meanings that can be explored both narratively and ethically, following Ricoeur’s stages of interpretation from literal understanding to philosophical reflection. The findings reveal that Serat Nitisruti not only reflects Javanese cultural morality but also conveys universal values that are in harmony with Islamic teachings. This study reinforces the view that local literary works can serve as a space for cross-cultural and interreligious dialogue, as well as a medium for transmitting inclusive humanistic values.